Gitelman syndrome associated with chondrocalcinosis: description of two cases - E. Filippucci; L. Di Geso; M. Tardella; G. Giacchetti; C. Bertolazzi; F. Silveri; M. Gutierrez; W. Grassi (PAGEPress Publications, 2011)
Gitelman syndrome is a rare inherited tubulopathy, characterized by hypomagnesemia, hypokalemia, metabolic alkalosis, hypocalciuria and hyperreninemic hyperaldosteronism. The clinical spectrum is wide and includes: cramps, myalgies, muscle weakness, until episodes of carpo-podalic spasm, tetania, rabdomyolisis and paralysis. Some cases have been described in literature underlining the association of this condition with chondrocalcinosis, as a typical example of hypomagnesemia-induced crystal deposition disease. The therapy of Gitelman syndrome consists on the administration of defective electrolytes, althought not always effective. We describe two cases of Gitelman syndrome associated with chondrocalcinosis showing the wide range of presentation of this clinical condition.